Enhancing Capacity of Healthcare Scholars and professionals in Responding to the Global Health Issues - Malini, Hema (De Gruyter, 2019)
Description The 2nd Andalas International Nursing Conference 2019 (AINiC 2019) "Enhancing the Capacity of Healthcare Scholars and Professionals in Response to Global Health Issues". The conference is a great opportunity and an inspiring occasion for research development learning, especially in the disseminating of new findings in nursing and to bring together the networking of nursing professionals, nursing researchers, and nursing educators. This will be an opportunity to encourage the emergence of academic culture in developing knowledge, proposing discourse about the latest issues, and discussion. AINiC 2019 will integrate various fields and aspects of nursing as a science from the perspectives of education, research, and practices that will reshape a better understanding and comprehensiveness of the knowledge. Aims: Accommodate and increase research contributions in the field of nursing and health Facilitate research publication. Improve a better understanding of nursing knowledge and nursing research Initiate mutual partnerships and cooperation between individuals and educational institutions Scopes: Research Practice Mental Health Health Management Clinical Science Advanced Practice Pediatric Health Community Health Maternal and Women's health Gerontology Global Health Issues Transcultural Disasters Health Policy New Emerging Diseases Technology and Info